Re-Irradiation in Squamous Cell Carcinoma of the Head and Neck - Barros João; Rodrigues Mónica; Leite Regina; Rothwell David; Pires Beatriz; Serra Tânia; Khouri Leila; Alves Paula (Forum of Clinical Oncology, 2023)
Re-irradiation as a therapeutic option for locoregional recurrence in patients with recurrent, persistent tumour or second primary malignant neoplasm has great advantages for locally advanced unresectable tumours.